'It's difficult to forecast your longer term career milestone': career development and insecure employment for research academics in Australian universities. (1st October 2016) - Broadbent, Kaye; Strachan, Glenda
ABSTRACT: Universities globally have undergone significant changes in the past three decades and Australia is no exception. The importance to universities of research has resulted in a surge in the employment of research focused academics in Australian universities. Findings from the 2011 Work and Careers in Australian Universities (WCAU) survey revealed 84% of research academics were employed on fixed-term contracts. To explore the impact of insecure employment for research academics we used the labour market segmentation literature to determine whether these academics constitute a 'secondary' labour force. Interviews with 18 research academics revealed insecure employment had negatively affected their career development. Responses indicated that it affected particularly their ability to publish productively, develop an independent research profile and form networks and collaborative connections. Insecure employment has a largely negative impact on research academics' careers and as a result they have become a 'secondary' labour force in universities.